GENDER REPRESENTATION AND GENERATION Z PERSPECTIVES ON MUSLIM FASHION TRENDS IN MALE GAZE STUDIES - Soraya, Syarifah; Mumtaazah, Yasmine; Surawan, Surawan (IAIN Bone, 2025)
This study explores Generation Z male perspectives on Muslim fashion trends in the context of male gaze theory and their implications for social norms in the digital era. The research aims to investigate how young Muslim men interpret Muslim women’s fashion on social media, how male gaze shapes their perceptions of piety and modesty, and how these perceptions influence gender interactions online. A simple mixed methods design was employed by combining quantitative survey data with qualitative insights from a Focus Group Discussion (FGD). The survey identified general patterns of perception, while the FGD provided deeper understanding of participants’ viewpoints. Quantitative data were presented in percentages, while qualitative data were analyzed thematically. The findings reveal diverse perceptions: some participants associated fashion with religious identity and moral character, while others viewed it as cultural expression and lifestyle. Most participants acknowledged engaging in judgment based on women’s clothing, reflecting the persistence of male gaze in digital interactions. Furthermore, all respondents agreed that social media strongly influences standards of appropriateness, highlighting its role in shaping collective norms through algorithms, comments, and viral trends. The study concludes that male Generation Z perceptions contribute to the construction of modesty standards and gender relations online, underscoring the need for digital literacy and gender-sensitive awareness to promote more inclusive interactions.